2021
DOI: 10.1111/imb.12693
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis revealsTORsignalling‐mediated plant flush shoots governingDiaphorina citriKuwayamaoviposition

Abstract: Asian Citrus Psyllid (ACP), Diaphorina citri, is a key vector transmitting the causative agent of Huanglongbing (HLB) disease. Population growth of ACP is evident after feeding on plant flush shoots, as they only oviposit here. However, the underlying mechanism as to why flush shoots govern oviposition is unclear. This study compares the fecundity and ovarian morphology of ACP between young flush and mature leaves. Furthermore, the transcriptome of mated females infesting Murraya paniculata was analysed. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In ACPs feeding on young shoots, psyllid female ovarian development was activated, inducing oviposition. However, silencing of the positive regulatory gene DcRheb in the target of rapamycin (TOR) pathway lowered ecdysone and juvenile hormone levels, suppressed vitellogenin synthesis, and reduced female reproductive capacity [86]. Genes in the TOR pathway, among others, have been proposed as the potent candidates for silencing to reduce the reproductive capacity of insects; however, if product of choice is an RNAi-based pesticide, it must be applied to shoots for successfully silencing the target transcripts.…”
Section: Acp Control Using Rnai Technologymentioning
confidence: 99%
“…In ACPs feeding on young shoots, psyllid female ovarian development was activated, inducing oviposition. However, silencing of the positive regulatory gene DcRheb in the target of rapamycin (TOR) pathway lowered ecdysone and juvenile hormone levels, suppressed vitellogenin synthesis, and reduced female reproductive capacity [86]. Genes in the TOR pathway, among others, have been proposed as the potent candidates for silencing to reduce the reproductive capacity of insects; however, if product of choice is an RNAi-based pesticide, it must be applied to shoots for successfully silencing the target transcripts.…”
Section: Acp Control Using Rnai Technologymentioning
confidence: 99%
“…The D. citri used in this study was collected on shrubs of Murraya paniculata near South China Agricultural University (SCAU), Guangzhou, China, and subcultured in the laboratory of the Engineering Research Center for Biological Control, Ministry of Education, SCAU. The culturing method was to simply allow the D. citri to feed on the host plant M. paniculata covered in a white nylon net bag in an incubator at 26 °C, 14 h light and 10 h dark photoperiod, and 60% ± 2% relative humidity (Guo et al ., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…These substances will be ingested by female D. citri , so changing their nutritional status after feeding on flush shoots (Sétamou et al ., 2016 ) and inducing them to lay eggs. Our previous research demonstrated that the expression levels of JH‐ and 20E‐related genes and VG increase after D. citri has fed on flush shoots (Guo et al ., 2021 ). The DcRheb (Ras‐homologue enriched in brain), DcRaptor (regulatory associated protein of mTOR), DcSin1 (target of rapamycin [TOR] complex 2 subunit MAPKAP1), and DcS6K (TOR complex 2 subunit MAPKAP1) genes in the TOR signaling pathway are also all upregulated after mated D. citri females have fed on flush shoots (Guo et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations